2018
DOI: 10.1093/cid/ciy531
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology of Nontuberculous Mycobacteria Infection in Children and Young People With Cystic Fibrosis: Analysis of UK Cystic Fibrosis Registry

Abstract: NTM infection is of increasing prevalence in the UK paediatric CF population. This study highlights the urgent need for work to establish effective treatment and prevention strategies for NTM infection in young people with CF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…Furthermore, it has been indicated that in humans the syndromes caused by NTM include progressive NTM pulmonary disease, superficial lymphadenitis, cutaneous disease and disseminated disease. Pulmonary NTM disease cases have been identified among patients with chronic obstructive pulmonary disease, asthma, cystic fibrosis, suspected pulmonary TB and chronic TB (Cadmus et al., 2016; Chanda‐Kapata et al., 2015; Gardner et al., 2019; Hoza et al., 2016; Nyamogoba et al., 2012; Shao et al., 2015). NTM are an important cause of disseminated infection and disease in people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been indicated that in humans the syndromes caused by NTM include progressive NTM pulmonary disease, superficial lymphadenitis, cutaneous disease and disseminated disease. Pulmonary NTM disease cases have been identified among patients with chronic obstructive pulmonary disease, asthma, cystic fibrosis, suspected pulmonary TB and chronic TB (Cadmus et al., 2016; Chanda‐Kapata et al., 2015; Gardner et al., 2019; Hoza et al., 2016; Nyamogoba et al., 2012; Shao et al., 2015). NTM are an important cause of disseminated infection and disease in people living with HIV.…”
Section: Discussionmentioning
confidence: 99%
“…[27]. Recently, a longitudinal study identified that NTM infection is increasing in prevalence in the UK pediatric CF population from 1.3% to 3.8% between 2010 and 2015 with a sample size of 5333 patients under 16 years of age [28]. One study performed in Israel found a significant association between Aspergillus species and NTM species in sputum cultures of CF patients [29].…”
Section: M Abscessus and Cystic Fibrosismentioning
confidence: 99%
“…The full texts of the remaining 38 records were read in full; 19 articles were excluded-seven because of the absence of a control group, one because of the small sample size (<6 NTM-positive patients), and 11 because of the lack of data on risk factors. A total of 19 studies 5,12,19,20,[24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] were finally included (Figure 1), totaling 23 418 patients, of whom 1421 (6%) patients were diagnosed as NTM positive.…”
Section: Study Selectionmentioning
confidence: 99%
“…The publication date of the included studies ranged from 1992 to 2019. Ten studies were conducted in Europe, 19,25,[27][28][29][30]32,33,35,37 seven in North America 5,12,24,26,34,36,38 and two in the Middle East 3,20 ( Table 1). Among the seven case-control studies, five were matched on age and sex, 19,24,27,29,32 one on respiratory function, 39 and one on cystic fibrosis transmembrane conductance regulator (CFTR) mutation.…”
Section: Description Of the Studiesmentioning
confidence: 99%